Intervensi Psikologi di Layanan Kesehatan Primer - Anita Novianty; Sofia Retnowati (Faculty of Psychology Universitas Gadjah Mada, 2016)
The prevalence of mental disorder is growing up every year and highly contributed on global mental health burden. Yet the people who got professional treatment was below average. There was a gap between the high prevalence of mental disorder cases and the number of people who got the proper treatment. Some literature reviews showed that patients with psychiatric symptom were found out in primary health care, but mostly the case was not recognized by health workers due to lack of knowledge and skills on mental health issues, as well as the fear of stigma by the patients. The delay on detection of mental disorder onset will affect the prognosis of patient’s mental health. It is indicated the real emergency on detecting mental disorder symptoms and delivering the initial psychological intervention at primary health care level. This paper highlighted the high pre valence of mental disorder cases in primary health care, evidence based psychological interventions that have been used to treat the mental disorder cases in primary health care, as well as the challenges and the opportunities of psychological intervention in primary health care from some literature reviews